INNOVATIVE DEVELOPMENT OF INDUSTRIAL ENTERPRISES IN THE MODERN BUSINESS ENVIRONMENT IN THE CONTEXT OF IMPLEMENTING THE SUSTAINABLE DEVELOPMENT GOALS OF UKRAINE - SOKOLOVA, Liudmyla; KODRUL, Ruslan; MANUILOV, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article proves that in the context of implementing the goals of sustainable development of Ukraine, the innovative activity of industrial enterprises, the development of which depends on investments, is an important vector. The dynamics of Ukraine’s positions in two international innovation ratings: Consolidated Innovation Index and Global Innovation Index for the period 2020-2024 are analyzed. It is shown that the attractiveness of Ukraine for investors is negatively affected by economic instability, which weakens the country’s position in international investment ratings. It is studied that ensuring sustainable competitive advantages, increasing the level of competitiveness of enterprises in the country’s industrial sector in the conditions of the modern turbulent external environment dependsontheintroduction of newknowledge-intensive production technologies and the creation of innovative products. An analysis of promising areas of research by scientists of the Ukrainian-speaking sector of the information field for the period 2010-2024 is carried out. The degree of relevance of various aspects of the innovative activity of industrial enterprises in comparison with enterprises as a whole is determined. The existence of gaps in research, establishing the significance of the components of innovative activity of enterprises of the real sector of the national economy for the further development of areas of scientific work has been revealed. It has been proven that the current situation in the economy of Ukraine opens up new opportunities for the development, first of all, of areas related to the innovative activity of industrial enterprises. The features of innovative development of enterprises, the essence and expediency of applying a marketing approach to the development and introduction of innovative products to the market in modern economic conditions have been considered. It has been established that an important factor in the competitiveness of an enterprise is the awareness of the key competencies of the enterprise. It has been shown that the market activity of domestic industrial enterprises is influenced by global megatrends of the VUCAandBANIworld. They form a mixed, mixed business environment, which produces the emergence of various risks of influence on the market activity of enterprises of the real sector of the economy of Ukraine. It has been proven that the influence of factors of the mixed business environment requires updating approaches to solving the problems of ensuring the innovative development of domestic industrial enterprises. The conclusion is made about the decrease in the level of innovative development due to the presence of certain objective and subjective problems. The directions of innovative development of industrial enterprises are formed on the principles of marketing, innovativeness, synergy, multiplication, riskiness, which together provide a comprehensive approach to solving the specified problem. The significant impact of the combination of different types of innovative risks on the innovative development and efficiency of the functioning of industrial enterprises of the country is studied.